Characterization of novel isoforms and evaluation of SNF2L/SMARCA1 as a candidate gene for X-linked mental retardation in 12 families linked to Xq25-26 - Lavigne Paul; Todd Matthew AM; Lazzaro Maribeth A; Vallee Dominic; De Maria Adriana; Picketts David J (BMC, 2008)
Abstract Background Mutations in genes whose products modify chromatin structure have been recognized as a cause of X-linked mental retardation (XLMR). These genes encode proteins that regulate DNA methylation (MeCP2), modify histones (RSK2 and JARID1C), and remodel nucleosomes through ATP hydrolysis (ATRX). Thus, genes encoding other chromatin modifying proteins should also be considered as disease candidate genes. In this work, we have characterized the SNF2L gene, encoding an ATP-dependent chromatin remodeling protein of the ISWI family, and sequenced the gene in patients from 12 XLMR families linked to Xq25-26. Methods We used an in silico and RT-PCR approach to fully characterize specific SNF2L isoforms. Mutation screening was performed in 12 patients from individual families with syndromic or non-syndromic XLMR. We sequenced each of the 25 exons encompassing the entire coding region, complete 5' and 3' untranslated regions, and consensus splice-sites. Results The SNF2L gene spans 77 kb and is encoded by 25 exons that undergo alternate splicing to generate several distinct transcripts. Specific isoforms are generated through the alternate use of exons 1 and 13, and by the use of alternate donor splice sites within exon 24. Alternate splicing within exon 24 removes a NLS sequence and alters the subcellular distribution of the SNF2L protein. We identified 3 single nucleotide polymorphisms but no mutations in our 12 patients. Conclusion Our results demonstrate that there are numerous splice variants of SNF2L that are expressed in multiple cell types and which alter subcellular localization and function. SNF2L mutations are not a cause of XLMR in our cohort of patients, although we cannot exclude the possibility that regulatory mutations might exist. Nonetheless, SNF2L remains a candidate for XLMR localized to Xq25-26, including the Shashi XLMR syndrome.